Faktor-faktor yang berhubungan dengan kelengkapan imunisasi dasar di wilayah Kerja Puskesmas Burnai Mulya tahun 2024 - Rejeki, Kadek Yupita; Afrika, Eka; Dharmayanti, Reffi; Dewi, Ratna (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Immunization is giving the body immunity against a disease by inserting weakened disease germs into the body so that the body is resistant to diseases that are endemic or dangerous for a person. According to WHO in 2019, the majority of children currently receive life-saving vaccines, during 2017 it was estimated that 116.3 million or around 86% of children, children who did not receive complete immunization had an impact on child deaths in the world in 2019 of 2.5 million cases. The aim of this research is to determine the relationship between maternal knowledge, family support and maternal trust in vaccines simultaneously with the completeness of basic immunization in the Burnai Mulya Community Health Center working area in 2024. Type and design of the research is quantitative using analytical survey methods with a cross-sectional approach. sectional. The population in this study were all mothers with babies aged 9-18 months who visited the Burnai Mulya Community Health Center, totaling 637 respondents. The sample used was 84 respondents. The sampling technique in this research used accidental sampling technique. The results of the univariate analysis were obtained from 84 respondents, there were 60 respondents (71.4%) in the category of providing complete immunization and in the category of providing incomplete immunization totaling 24 respondents (28.6%). The results of the chi-square statistical test showed that the knowledge variable was ρ value = 0.002, the family support variable was ρ value = 0.021 and the mother's trust variable in vaccines was ρ value = 0.040, which was smaller than α=0.05, indicating that there was a significant relationship between knowledge, family support and trust. mothers on vaccines with complete basic immunization in the Burnai Mulya Community Health Center working area in 2024. Suggestions for the Burnai Mulya Community Health Center can provide information or consideration for policy makers to develop a solution to the problem of providing complete basic immunization to babies aged 9-18 months and provide information regarding Factors associated with providing complete basic immunization to babies aged 9-18 months